2017
DOI: 10.1101/129577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A chromatin extension model for insulator function based on comparison of high-resolution chromatin conformation capture and polytene banding maps

Abstract: Insulator proteins bind to specific genomic loci and have been shown to play a role in partitioning genomes into independent domains of gene expression and chromatin structure. Despite decades of study, the mechanism by which insulators establish these domains remains elusive. Here, we use genome-wide chromatin conformation capture (Hi-C) to generate a highresolution map of spatial interactions of chromatin from Drosophila melanogaster embryos. We show that from the earliest stages of development the genome is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Indeed, this proposal has been confirmed experimentally by comparing the molecularly mapped band/interband borders with the positions of TADs [ 18 ]. This correlation has been comprehensively analyzed by Eagen et al [ 20 ] who demonstrated that TAD borders matched the flanking regions of large bands found in polytene chromosomes and by Stadler and Eisen [ 21 ]. These studies have thus reinforced the hypothesis on the existence of a shared plan of interphase chromosome organization.…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, this proposal has been confirmed experimentally by comparing the molecularly mapped band/interband borders with the positions of TADs [ 18 ]. This correlation has been comprehensively analyzed by Eagen et al [ 20 ] who demonstrated that TAD borders matched the flanking regions of large bands found in polytene chromosomes and by Stadler and Eisen [ 21 ]. These studies have thus reinforced the hypothesis on the existence of a shared plan of interphase chromosome organization.…”
Section: Introductionmentioning
confidence: 97%